The Effectiveness of Using Lectora Inspire-Based Media on Class XI Craft Subjects at Muhammadiyah Sidrap Vocational High School - Darwis, Irma Aswani; M, Usman; Takdir, Muhammad; Hermansyah, Sam; Zain, Suardi (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The population of this study were all grade XI students at SMKS Muhammadiyah Purpose. The sample of this study used the totality sampling technique, namely taking samples as a whole, so that researchers took samples from the entire population of 31 people. Method. This study uses quantitative methods with the type of experimental research that aims to determine the effectiveness of using Inspire Lectora-based media in Class XI Workshop Subjects at SMKS Muhammadiyah Sidrap. Results. The results showed that the average posttest result was higher at 83%, while the pretest result was 50.8%. Based on the results of data analysis, it is concluded that the learning outcomes of students who use Lectora Inspire-based media in Craft learning are better than the learning outcomes of students who do not use Lectora Inspire-based media in class XI SMKS Muhammadiyah Sidrap. Conclusion. This shows that the use of Lectora-based media in Class XI Workshop subjects at SMKS Muhammadiyah Sidrap is declared effective.